Cytoplasmic RNA and nuclear changes detected cytochemically during the degeneration of salivary glands of the tick Rhipicephalus sanguineus (Latreille, 1806) (Acari, Ixodidae) - Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The present study reports cytochemistry data about salivary glands of females (unfed, engorged, and at day three post-engorgement) and males (unfed, at day seven post-attachment, and at days three and seven post-detachment from the host) of the tick Rhipicephalus sanguineus. The results revealed nuclear changes in engorged females and at day three post-engorgement, and in males in all stages (except unfed). These changes were more prominent in females. Cytoplasmic changes were also observed in cells of all acini of males and females.In types II and III acini of engorged females, nuclear changes were observed in the shape (irregular, with blebs, fragmenting or fragmented), size (enlarged or reduced), and arrangement and condensation level of chromatin (marginal or as blebs). Changes were also detected in nucleoli, regarding their shape (fragmenting or fragmented), size (enlarged), and location (central, marginal or as blebs). Some nucleoli were also compacted or disorganized. In females at day three pos-enuorgement, all acini exhibited similar changes to those observed in engorged females. RNA staining was stronger in cells of engorged females than those at day three post-engorgement.In males at day seven post-attachment, cells of types II, III, IV acini presented changes in the size of the nucleus and condensation level of chromatin similar to those of females. The shape of the nucleus was round, irregular or undergoing fragmentation, and the chromatin was located at the margin or throughout the nucleus. The changes in the nucleolus were similar to those of females, regarding size and organization, although round-shaped and in the central location. In males at day three post-detachment, cells of all acini exhibited nuclear changes similar to those of males at day seven post-attachment, in addition to the fragmentation of the nucleolus. At day seven post-detachment. changes were detected in all acini similar to the observed in males at day seven post-attachment. Regarding cytoplasmic RNA, staining was prominent in males at day seven post-attachment and weak in those at day seven post-detachment from the host.In females as well as males, different RNA staining patterns in the cytoplasm and nuclear changes characterized apoptotic cell death. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Rhipicephalus sanguineus; Salivary gland; females; males; chromatin; nucleolus; Apoptosis